CT ventriculographic identification and neuroendoscopic treatment of acquired hydrocephalus due to cerebral aqueduct lesions: a two-case report - Liu, Kai; Feng, Yuheng; Wang, Shuli; Zhang, Yubo; Ji, Xiaoxuan; Li, Qiang; Luo, Xiaodong (Frontiers in Oncology, 2026)
Hydrocephalus secondary to cerebral aqueduct lesions poses significant diagnostic and therapeutic challenges, particularly when causative lesions are occult on conventional neuroimaging. We present two pediatric cases of acquired obstructive hydrocephalus, in which routine laboratory tests were unremarkable except for mildly elevated tumor markers. Both patients exhibited acute symptoms of intracranial hypertension. Magnetic resonance imaging (MRI) demonstrated supratentorial hydrocephalus with periventricular edema but failed to visualize a definitive obstructive lesion. Subsequent cerebral ventriculography revealed aqueductal filling defects located at the aqueductal inlet along the floor of the third ventricle. Neuroendoscopic resection of the intraventricular lesions was successfully performed through a right frontal transventricular approach. Histopathological examination played a pivotal role in management: Both cases were postoperatively diagnosed as mixed germ cell tumors. Case 1 received postoperative chemoradiotherapy, whereas Case 2 was treated with postoperative chemotherapy alone. Both patients achieved rapid and sustained symptom relief, with no postoperative complications or recurrence observed during the 12-month follow-up period. These cases underscore the diagnostic value of ventriculography in identifying occult aqueductal lesions and highlight the dual diagnostic and therapeutic utility of neuroendoscopic resection, which provides a definitive histological diagnosis and restores cerebrospinal fluid circulation.